P05.40 Clinical and radiological outcome of vestibular schwannomas (Koos grade I - IV) after stereotactic radiosurgery. (19th September 2018) - Daniel, R; Poehlmann, L; Treuer, H; Kocher, M; Jablonska, K; Grau, S; Ruge, M
Abstract: Background: In the management of vestibular schwannoma (VS) stereotactic radiosurgery (SRS) has evolved as widely accepted treatment option for small-sized tumors (Koos I and II). For larger VS (Koos III and IV) microsurgery is treatment of choice. However, for patients not suitable for microsurgery SRS might also be an alternative that balances tumor control, hearing preservation and adverse effects. The purpose of this analysis was to evaluate the efficacy and toxicity of SRS for different Koos grades including VS Koos III and IV. Material and Methods: In this single center retrospective analysis (1991 - 2016) we included all patients with previously untreated VS who underwent single session LINAC or Cyberknife® based SRS. Patient data were analyzed and correlated using cox proportional hazard model in terms of the different Koos grades. Data analysis considered tumor control, preservation of serviceable hearing, course of median pure tone averages (PTA) at last follow up and procedure related early and late adverse events rated by Common Terminology Criteria for Adverse Events (CTCAE; v4.03). Results: 265 patients (median age 59 years, range 17–84) were identified with a mean follow-up of 50.9 months (range 3–265 months). Mean tumor volume was 1.8 ml (range 0.1–23.7 ml). The mean marginal dose was 12.4 Gy ± 0.8 (range 11–20) and the mean isodose was 69.3 % ± 12.5 (range 32.9–86.2). 193 patients were considered as Koos grade I or II and 72 patients as grade III or IV. Actuarial tumor control was 98.5%, 88% and 88% after 2, 5 and 10 years respectively without significant difference between Koos grades I/II vs III/IV (hazard ratio (HR) 1.1, p=0.8, 95% CI, 0.4–3.6). Likewise, median PTA increase of Koos I/II tumors compared to Koos III/IV tumors revealed no significant difference (HR 0.5, p=0.07, 95% CI, 0.3–1.0). New permanent CN V and VII impairment could be objectified in 7.1% (n=19/265). The rate of permanent CN V and CN VII impairment showed no significant difference between Koos grades I/II vs III/IV (HR 0.5, p=0.07, 95% CI, 0.3–1.0). Conclusion: SRS for VS shows reliable long term tumor control and a high rate of hearing preservation and with low permanent side effects. Therefore, SRS can be proposed as safe and effective treatment option for VS, even with higher Koos grades.